The effect of holding a workshop (group and face-to-face training method) on nutrition adjustment on anthropometric indices in children with chronic liver disease - Zahra Namjou; Seyed Ali Jafari; Aramesh Rezaeian; Majid Ghayour-Mobarhan; Elham Shahraki Moghadam (Journal of Education and Health Promotion, 2022)
BACKGROUND: Complications of chronic liver disease (CLD) in children play an important role in mortality and disability. This disease is one of the health problems of the country and due to its chronic and irreversible disease, it needs care and treatment education programs. Therefore, this study was performed to determine the effect of nutrition adjustment training program on anthropometric indices in children with CLD. MATERIALS AND METHODS: This clinical trial study was performed on 75 children (45 in the intervention group and 30 in the control group) with CLD in the nutrition clinic of Ghaem Educational-Research Center in Mashhad. Children and caregivers with inclusion criteria entered the study after completing written consent. Anthropometric indices (abdominal circumference, body water level, body fat, height, weight, body mass index, arm circumference) were measured and recorded in children at the beginning of the study. Children and their caregivers were randomly divided into control and intervention groups. The intervention group underwent nutritional adjustment (calculation of energy and carbohydrates, lipids and proteins, vitamins and minerals, calculation and selection of diet) training (face to face) for 6 sessions (each session 90–120 min, three times a week for 2 weeks). Twelve weeks after the start of the study, children in both intervention and control groups were evaluated for anthropometric indices. The collected data were analyzed by SPSS software version 16 and descriptive and analytical statistical tests (Mann–Whitney and Wilcoxon). RESULTS: The results of Wilcoxon statistical test showed that children in the intervention group at the end of the study compared to the beginning of the study had significant changes in scores around the abdomen (P = 0.001), total body water (P = 0.009), total fat (0.001 > P), height (P = 0.001), weight (P < 0.001), body mass index (P < 0.001), arm circumference (P < 0.001). The mean scores at the end of the study increased compared to the beginning of the study, but the mean scores of the studied indices in the control group did not change significantly. CONCLUSION: The results of this study showed that diet adjustment training program can be effective on anthropometric indices of children with CLD. For this purpose, the use of this educational method is recommended to improve the anthropometric indices of these children.